2021
DOI: 10.2196/preprints.30709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online-Delivered Group and Personal Exercise Programs to Support Low Active Older Adults’ Mental Health During the COVID-19 Pandemic: Randomized Controlled Trial (Preprint)

Abstract: BACKGROUND In response to the COVID-19 pandemic, experts in mental health science emphasized the importance of developing and evaluating approaches to support and maintain the mental health of older adults. OBJECTIVE The aim of this study was to assess whether a group-based exercise program relative to a personal exercise program (both delivered online) and waitlist control (WLC) can improve th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The social aspect of exercise programs may be more important for older adults, given their higher risk of social isolation and loneliness (2), which can be further intensified during unpredictable situations such as ongoing social restrictions of a pandemic (69). Similar studies have also suggested that promoting meaningful social interaction can positively impact the physical and mental health of older adults (68, 70), particularly during quarantine periods (71,72).…”
Section: Discussionmentioning
confidence: 68%
“…The social aspect of exercise programs may be more important for older adults, given their higher risk of social isolation and loneliness (2), which can be further intensified during unpredictable situations such as ongoing social restrictions of a pandemic (69). Similar studies have also suggested that promoting meaningful social interaction can positively impact the physical and mental health of older adults (68, 70), particularly during quarantine periods (71,72).…”
Section: Discussionmentioning
confidence: 68%